IMPACT OF PREPOTENCY IN COCONUT PRODUCTIVITY - K. U. K. NAMPOOTHIRI (International Coconut Community, 1991)
Identification of prepotent palms among the commonly grown tall cultivars helps in improving the yield substantially. The efforts made in selection of prepotent mother palms and identification at seedling stage is briefly reviewed. The merits and demerits of progeny testing are discussed and future lines of work are indicated.